Trade Networks in Latin America : Spatial Inefficiencies and Optimal Expansions - Gorton, Nicole; Ianchovichina, Elena (World Bank, Washington, DC, 2021)
How do trade connectivity issues affect the efficient spatial distribution of economic activity within and across countries in Latin America This paper uses a spatial general equilibrium framework to construct optimal transport networks and optimal expansions to existing networks in most Latin American countries, as well as within MERCOSUR and the Andean Community. The paper assesses the average annual welfare losses due to inefficient domestic road networks in Latin America at 1.7 percent, ranging from 2.5 percent in Brazil to 0.2 percent in El Salvador. Spatial misallocation of transnational road networks is associated with annual welfare losses of 1.8 percent in MERCOSUR and 1.6 percent in the Andean Community. Optimal investments in improvements and expansions of existing networks can correct these inefficiencies and reduce spatial inequality within countries. These investments correlate relatively well with World Bank road projects because both the model and the World Bank prioritize investments in high population areas. Transnational road improvements benefit the most the least developed country in each trade bloc. The results are robust to changes in data sources and model assumptions.